Legal analysis of the distribution of inheritance in the form of land rights to foreign national heirs - Oktavia, Sri Libra; Respationo, Soerya; Erniyanti, Erniyanti; Nofrial, Ramon; Tartib, Muhammad (Journal of Multidisciplinary Academic and Practice Studies, 2023)
Purpose: This study aims to determine the implementation of the distribution of inheritance in the form of land rights to heirs with foreign citizenship and to identify the factors that become obstacles/constraints and solutions in the distribution of inheritance in the form of land rights to heirs with foreign citizenship. Research methodology: This study uses sociological or empirical legal research, which mainly examines primary data, such as materials that bind legislation. Results: The results showed that inheritance can be distributed to heirs with foreign citizenship, but the foreign nationals must transfer the land to Indonesian citizens within one year or change their rights to use rights. Conclusion: Foreign nationals are permitted to inherit land rights in Indonesia; however, regulations require them to transfer ownership to Indonesian citizens or convert the rights into use rights within a year. This ensures the protection of national land sovereignty while providing limited options for foreign heirs. Limitation: This study is limited to an examination of Indonesia’s legal framework and empirical data, without a broader comparative analysis across regions or countries. These limitations may affect the generalizability of our findings. Contribution: This study provides a comprehensive overview of the legal framework governing the inheritance of land rights by foreign nationals in Indonesia. It also identifies and discusses the key challenges faced by foreign national heirs during the inheritance process.